Rescue thrombolysis for medium vessel occlusion (RESCUE-TNK): Rationale and design of a phase 2 randomized trial - Hu, Hai-Zhou; Qiu, Jing; Li, Wei; Nguyen, Thanh N.; Wang, Feng; Li, Di; Shi, Huai-Zhang; Wang, Shou-Chun; Wei, Ming; Chen, Hui-Sheng (Frontiers in Neurology, 2023)
Background: The best reperfusion strategy for medium-sized vessel occlusion (MeVO) is not well established. Given the proven treatment effect of intra-arterial thrombolysis in patients with large vessel occlusion (LVO), we hypothesized that intra-arterial tenecteplase (TNK) could increase the recanalization rate of MeVO and thus improve clinical outcome. Aims: To explore the safety and efficacy of intra-arterial TNK in patients with MeVO. Sample size estimates: A maximum of 80 patients are required to test the superiority hypothesis, using power = 80% and α = 0.025 to conduct the one-sided test. Design: Rescue treatment for mEdium veSsel oCclUsion by intra-artErial TNK (RESCUE-TNK) is a pilot, randomized, open-label, blinded end point, and multicenter trial. Eligible patients including primary MeVO as detected by the first DSA examination or secondary MeVO after endovascular treatment (EVT) for LVO will be assigned into the experimental group and control group as a ratio of 1:1. The experimental group will be treated with intra-arterial TNK (0.2-0.3 mg/min, for 20-30 min) via a microcatheter placed proximal to the site of occlusion, and the control group will be treated with routine therapy. Both groups of patients will be given standard stroke care based on the guidelines. Outcome: The primary efficacy end point is successful recanalization of MeVO, defined as the expanded treatment in cerebral ischemia (eTICI) score 2b67-3 after the procedure, while the primary safety end point is symptomatic intracranial hemorrhage (sICH), defined as National Institutes of Health Stroke Scale score increase ≥4 caused by intracranial hemorrhage within 24 (-6/+24) hours after randomization. Conclusions: The results of RESCUE-TNK will provide evidence for the efficacy and safety of intra-arterial TNK in the recanalization of patients with MeVO.